GEOPHYSICAL METHODS APPLICATION FOR PIPELINE TRANSPORT SYSTEMS - Глоба, Р.; Зінченко, I.; Глоба, Я.; Дзюба, О. (Київський національний університет імені Тараса Шевченка, 2017)
Set of geophysical methods to engineering surveys when designing and operating linear underground constructions of pipeline transport is proposed to apply. The study allows to identify the area's best fitting for laying and operating the pipeline transport system. The paper provides a complex of geophysical methods to guarantee safety standards on the pipeline transport systems when affected by natural and anthropogenic hazards. During implementation of this study, the feasibility of using digital satellite images for monitoring of pipeline transport facilities was confirmed. The paper proposes the application of complex of traditional electrical methods to the pipeline transportation system, the latter being typified as a complex engineering construction. Electrical methods, such as vertical electrical sounding, symmetrical electrical profiling, gradient potential method and self potential method were used to identify possible areas of corrosion on the underground pipeline of filling station "Kharkiv-4". The low apparent resistivity and high negative spontaneous potential values indicate that the soil is very corrosive and it is possible to have the pipeline failure in the future. Electrical geophysical investigations along buried pipelines should be undertaken for the early detection and prevention of pipeline failure with its negative environmental and economic consequences.

Запропоновано використання комплексу геофізичних досліджень для інженерних вишукувань при проектуванні і експлуатації лінійних підземних споруд трубопровідного транспорту. Показано можливість вибору ділянок для будівництва та експлуатації трубопровідних транспортних систем. Розкрито ефективність комплексного застосування геофізичних методів при обґрунтуванні заходів захисту трубопровідних транспортних систем від впливу природних і техногенних процесів. Для визначення можливих ділянок корозії на підземному вхідному газопроводі АГНКС (автомобільна газонаповнювальна компресорна станція) "Харків-4" були проведені дослідження методами електророзвідки: ВЕЗ (вертикальне електричне зондування), "віддаленого електрода", вимірювання градієнт потенціалу і СЕП (симетричне електричне профілювання). Низький позірний опір і високі негативні значення потенціалу є ознаками того, що ґрунти схильні до корозії і є ймовірність пошкодження трубопроводу в майбутньому. Підтверджено, що електричні геофізичні дослідження уздовж підземних трубопроводів слід проводити для раннього виявлення та профілактики пошкоджень трубопроводу з негативними екологічними та економічними наслідками.
ГЕОФІЗИЧНІ МЕТОДИ ДОСЛІДЖЕНЬ ТРАС ТРУБОПРОВІДНИХ ТРАНСПОРТНИХ СИСТЕМ
Keywords: corrosion; pipeline systems; engineering surveys; VES; SEP; the method of "remote electrode"; measuring potential gradient; корозія; ВЕЗ; СЕП; метод "віддаленого електрода"; вимірювання градієнт потенціалу